Rumah Tradisional Jawa Dalam Sudut Pandang Religi - Joko Budiwiyanto (Institut Seni Indonesia Surakarta, 2013)
This article is the result of research on traditional Javanesehouse in a religious viewpoint.The purpose of the study wouldlike to know the value of religious construction that is built intraditional Javanese house layout.To achieve the goal be takenthrough research with qualitative research methods, data sourcesused are literature, artifacts, and informants.The analysis modelis an interactive model of analysis.The results found that the Javanesecommunity in building his house, through some kind ofconsideration,such as site selection, building materials, home establishmenttime, ceremony to build a house, division of space,direction toward, until the determination of the type of ornamentsthat have a symbolic meaning.The process of ceremony is in-1 Joko Budiwiyanto, S.Sn.,M.A. Staf Pengajar Prodi Desain Interior Jurusan DesainFSRD ISI Surakarta